Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai di Perusahaan Daerah Air Minum Tirta Kencana Kabupaten Jombang - Yiyin Mardiana Puspitasari; Lilis Sugi Rahayu Ningsih (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
The goals on the observation where examine any impact between works environment anddisciplin toward employesed performances of this company on Tirta Kencana RegionalWater Supply in Jombang Regency. This used quantitative research methods and causalapproach. The number off samples was 54 employees and was using questionnaire asdata collectionss techniques. Hipothesis have influenced simultaneous have influencedsimultaneous and causal approach, determination coefficiens test (r) of multiple linearsregrestion analysys. The result in observation of shown up that : Working environmentand working disciplin have influenced simultaneous toward employees performance inthe company of Tirta Kencana Regional Water Supply in Jombang Regency